Pengaruh Persistensi Laba, Kekuatan Laba, Konservatisme Akuntansi, dan Struktur Modal terhadap Penilaian Ekuitas: Studi Empiris Perusahaan Sektor Kesehatan yang Terdaftar di BEI Tahun 2018-2023 - Wijayanti, Friska Tri; Nufaisa, Nufaisa; Koerniawati, Dwi; Junjunan, Mochammad Ilyas (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to determine the partial and simultaneous effects of earnings persistence, earnings power, accounting conservatism and capital structure on equity valuation. The type of research used is quantitative research with secondary data, in the form of financial and annual reports obtained from the official website of the Indonesia Stock Exchange. The population used is in the form of health sector companies listed on the Indonesia Stock Exchange in 2081-2023. The sampling method was purposive sampling method and obtained 48 samples. The data analysis technique uses panel data regression analysis. The novelty in this research lies in the capital structure variable, the population in the form of health sector companies and the use of a 6-year period. The results of the study represent that partially earnings persistence and capital structure have no significant effect on equity valuation. While earnings power and accounting conservatism have a significant effect on equity valuation. While simultaneously earnings persistence, earnings power, accounting conservatism and capital structure have a significant effect on equity valuation.